Identification du comportement rheologique par analyse inverse - Gavru, Adinel; Massoni, Elisabeth; Chenot, Jean-Loop (European Journal of Computational Mechanics, 1998)
The use of the inverse metlwd principle for analysing rheological tests is presented. It is based on the finite element simulation, capable of taking into account the whole complexity of the test, especially in terms of self-heating and strain localisation phenomena. The identification of rheological parameters is then ensured by solving an inverse problem. The principle is to find the rheological coefficients which permit one to obtain the optimal comparison between the experimental measurements and the numerical resolution.